2022
DOI: 10.1149/2162-8777/ac6979
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Skin Layer on Brush Loading, Cross-Contamination, and Cleaning Performance during Post-CMP Cleaning

Abstract: The use of polyvinyl acetal (PVA) brushes is one of the most effective and prominent techniques applied for the removal of chemical mechanical planarization (CMP) contaminants. However, the brush can be a source of defects by entrapping the abrasives inside its porous structure during brush scrubbing. In this study, the effect of brush top skin layer was extensively studied on contamination, cross-contamination, and cleaning performance by comparing brushes with and without skin layer. The presence of a dense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…However, the presence of the skin layer is necessary as it gives higher cleaning efficiencies. 64 Conventional brush break-in process (cleaning through pressurized water), 59 ultrasonic assisted physical break-in process (highly efficient) 65 or dipping in chemicals, 66 or scrubbing on dummy wafers 67 could be employed for the pretreatment of the incoming brush (brush conditioning) to avoid any contamination. Lee et al 56 compared different techniques and concluded that the ultrasonic-assisted physical break-in process is highly competent for rapid contaminant removal from the PVA brush.…”
Section: Post-cmp Cleaning Process and Equipmentmentioning
confidence: 99%
“…However, the presence of the skin layer is necessary as it gives higher cleaning efficiencies. 64 Conventional brush break-in process (cleaning through pressurized water), 59 ultrasonic assisted physical break-in process (highly efficient) 65 or dipping in chemicals, 66 or scrubbing on dummy wafers 67 could be employed for the pretreatment of the incoming brush (brush conditioning) to avoid any contamination. Lee et al 56 compared different techniques and concluded that the ultrasonic-assisted physical break-in process is highly competent for rapid contaminant removal from the PVA brush.…”
Section: Post-cmp Cleaning Process and Equipmentmentioning
confidence: 99%